Child Abuse in the Family: An Analytical Study - D Shojaeizadeh (Tehran University of Medical Sciences, 2001)
The prevalence of child abuse in the world is 47 per 1000. According to the Child Protective Service agency (CPS) more than 3 million children were abused in the USA in 1998. There was 1.7% increase in comparison with 1996. The prevalence of child abuse in the USA is 15 per 1000. A crosssectional study was conducted in order to determine the frequency, and influential factors on child abuse among families in Tehran. A sample of 420 students was selected from secondary school girls in Tehran in 1999. A questionnaire was used for data collection, and the collected data were analysed through statistical tests such as X2 and other forms of descriptive tests. The findings of research showed that in terms of abnormal (unexpectedly bad) behaviour, 28% of the sample were faced quarrelsome and bitted by their fathers. The mothers' reactions for similar behaviour were more or less the same: 34.9% quarrelsome and 7% bitting. Child abuse, physically and emotionally, has had significant relation with socioeconomic status of families as well as having interaction with mentally ill or addicted person(s) among families. Mothers' employment, religious beliefs, and parents' educational attainments also demonstrated significant relations with child abuse. A statistically significant relationship has also been found between mothers' employment, addicted or mentally ill person among family members, and doubtful child sexual abuse.To prevent child abuse the following actions should be taken: Education of parents about children rights and how to treat their children. Establishment of centers to protect the children at risk. Education of young couples to take more reponsibility of having children.